The Lateglacial to early Holocene tephrochronological record from Lake Hämelsee, Germany: a key site within the European tephra framework - Jones, Gwydion; Lane, Christine S.; Brauer, Achim; Davies, Siwan M.; De Bruijn, Renée; Engels, Stefan; Haliuc, Aritina; Hoek, Wim Z.; Merkt, Josef; Sachse, Dirk; Turner, Falko; Wagner-Cremer, Friederike (Wiley, 2017)
Here we present the results of a detailed cryptotephra investigation through the Lateglacial to early Holocene transition, from a new sediment core record obtained from Lake Hämelsee, Germany. Two tephra horizons, the Laacher See Tephra (Eifel Volcanic Field) and the Saksunarvatn Ash (Iceland), have been previously described in this partially varved sediment record, indicating the potential of the location as an important Lateglacial tephrochronological site in northwest Europe. We have identified three further tephra horizons, which we correlate to: the c. 12.1 ka BP Vedde Ash (Iceland), the c. 11 ka BP Ulmener Maar tephra (Eifel Volcanic Field) and the c. 10.8 ka BP Askja-S tephra (Iceland). Three additional cryptotephra deposits have been found (locally named HÄM_T1616, HÄM_T1470 and HÄM_T1456-1455), which cannot be correlated to any known eruption at present. Geochemical analysis of the deposits suggests that these cryptotephras most likely have an Icelandic origin. Our discoveries provide age constraints for the new sediment records from Lake Hämelsee and enable direct stratigraphical correlations to be made with other tephra-bearing sites across Europe. The new tephrostratigraphical record, within a partially varved Lateglacial sediment record, highlights the importance of Lake Hämelsee as a key site within the European tephra lattice.